SOMATOSENSORY AND MOTOR EVOKED POTENTIALS AS PROGNOSTIC INDICATOR OF WALKING AFTER SPINAL CORD INJURY (International Journal of Physiotherapy, 2015)
Background: Walking recovery is one of the main goals of patients after SCI. Walking is rated as primary goal and desire (together with bladder and bowel function) irrespective of the level of lesion. Past literature terms walking as long-term outcome or as a primary means of mobility after SCI.In patients with SCI clinical and electrophysiological examinations are directed towards predicting functional recovery.Methods: A systematic research of all papers was made by the authors using the PRISMA 2009 guidelines. Using the various search engines 56 articles was found and 22 were selected for the present study. Out of these 17 were included for the final stageResult: Electrophysiological measures can provide information that complements clinical assessments such as the American Spinal Injury Association sensory and motor scores in the evaluation of outcomes after spinal cord injury (SCI).Conclusion: The authors review and summarize the literature regarding tests that are most relevant to the study of SCI recovery—in particular, motor evoked potentials and somatosensory evoked potentials (SSEPs). Both SSEP and MEP provide data clinically significant as a prognostic indicator.